Quantifying soil dynamics for agricultural use in the city of Yaoundé (Cameroon) - (:unkn) unknown (My University, 2022)
By 2025, nearly 50% of the population of sub-Saharan Africa will be urban. In Yaoundé, the capital of Cameroon, urbanization is ranked among the most accelerated in sub-Saharan Africa (the average annual growth rate varies around 5%). These statistics emerge in a context marked by underfeeding, malnutrition, and multidimensional poverty in crowded city neighborhoods. According to the literature, this urbanization poses a threat of disappearance of land used for agriculture. To understand this issue, a study was conducted in Yaoundé. The main objective was to analyze the impact of the evolution of urbanization on the evolution of urban agriculture in Yaoundé. Landsat 7 and 8 images of Yaoundé dated 18 May 2000 and 4 May 2015 respectively were uploaded to earthexplorer®. Land use maps and a land use change map with descriptive statistics were produced using the ENVI Version 521® classification and maximum likelihood change analysis algorithm respectively. Then, a diachronic analysis was performed. Losses of land for agricultural use, estimated at 2855.86 ha, were recorded over the observation period, particularly in the suburban areas of Yaoundé.
Keywords: African Research